Miniature cheeses made with blends of chymosin and a vegetable rennet from flowers of Silybum marianum: Enzymatic characterization of the flower-coagulant peptidase - Colombo, Maria Laura (2018)
Binary blends of S. marianum–flower extract and chymosin, as coagulant preparations, enabled the manufacture of miniature cheeses with distinctive characteristics compared to those of chymosin-renneted cheeses. The physicochemical parameters, sensory attributes of the cheeses, and in-vitro water-soluble antioxidant activity were analyzed and compared to those properties obtained from control chymosin-renneted cheeses. The preponderant proteolytic constituent in the flower extract was isolated in a two-step-purification protocol. The thus purified aspartic peptidase was maximally active at acidic pHs and exhibited a preference for peptide bonds between hydrophobic residues. Enzymologic characterization revealed differences in the kinetic parameters and specificity compared to other enzymes employed, such as rennet. S. marianum–flower extract, as a source of peptidase with distinctive characteristics, is a suitable substitute for chymosin in miniature-cheese production. The addition of vegetable rennet contributed to the development of an intense aroma and conferred antioxidant activity to the cheeses and wheys.